Restrukturisasi Sistem Fraksi Di DPR RI Guna Mewujudkan Pembangunan Demokrasi - Patricia, Tiara; Gunawan, Chyntia; Yudhistira, Dhiwatsani (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Abstract In the Indonesian constitution, it is explained that the sovereignty of the Indonesian state is in the hands of the people as stated in Article 1 paragraph (2) of the 1945 Republic of Indonesia Constitution so all actions taken by the state must side with the interests of the people. Indonesia is a country that adheres to a democratic system, which means from the people to the people. Indonesia is a country of law so it has a logical consequence that every state action must have a clear legal basis. The DPR is a legislative institution that represents the interests of the people as explained in Article 20 paragraph (1) of the 1945 Republic of Indonesia Constitution states that: